Virtualisasi Pembelajaran Pendidikan Agama Islam Di Era Revolusi Industri 5.0 Dalam Buku Karya Asfiati - Nur Inayah Wardani; Muyasaroh; Man Arfa Ladamay (STIT Muhammadiyah Paciran, 2022)
The purpose of Islamic education is to emphasize the formulation in education that distinguishes between Islamic education and education in general, namely by looking at the limitations in learning taught by students by emphasizing Islamic education. It is hoped that this Islamic education will be able to bring good people and also have character in accordance with the teachings of Islam. In the teachings of Islam, good character or morals are emphasized because it really reflects someone who has faith and is also devoted to Allah SWT. The purpose of this study was to find out how Islamic Religious Education Learning in the Industrial Revolution Era 5.0 in Asfiyati's Book The type of research used was descriptive qualitative research with a library research approach. Data collection is carried out in the form of documentation, namely by collecting data from various literature sources related to the research conducted. Analysis of the data using the method of content analysis. The informant in the interview conducted by the author is Ms. Asfiyati Himself.